Alternate heat and mass transfer absorption performances on staggered tube bundle with M–W corrugated mesh guider inserts. (June 2016) - Chen, Yaping; Cao, Ruibing; Wu, Jiafeng; Yi, Zheyu; Ji, Guangju
Highlights: Any two adjacent mesh inserts in tube bundle are of mirror symmetry like M and W. Performances of tubular absorbers with and without M–W mesh guiders were compared. M–W mesh guider leads uniform and dual-side solution film for adiabatic absorption. CFD models were established for falling film absorption on both tubes and meshes. Film coverage, temperature, concentration and h.t.c. distributions are demonstrated. Average heat and mass transfer increments of alternating absorber are 33.4% and 55%. Abstract: A new alternate absorption scheme of both horizontal tubular cooling absorption and mesh layer adiabatic absorption was investigated with longitudinal corrugated M–W mesh guiders inserted to the gaps of the staggered horizontal tube bundle, leading solution film flows from the lower edge of each tube to the upper edges of its lower position neighbouring tubes at both sides. The mirror symmetric M–W mesh guiders facilitate uniform distribution and dual-side exposing solution film to the vapour for adiabatic mass transfer. The VOF CFD models were established for vapour absorption with aqueous LiBr solution falling film on the alternate absorber and bare tube one. The distributions of liquid film, temperature and concentration of the solution and local heat transfer coefficient on the tube surfaces were demonstrated for both absorbers. The simulation results demonstrated that the average heat and mass transfer coefficients with the alternating absorber are respectively 33.4% and 55.4% higher than those of the bare tube one.